2012
DOI: 10.1371/journal.pone.0032745
|View full text |Cite
|
Sign up to set email alerts
|

Tractography Delineates Microstructural Changes in the Trigeminal Nerve after Focal Radiosurgery for Trigeminal Neuralgia

Abstract: PurposeFocal radiosurgery is a common treatment modality for trigeminal neuralgia (TN), a neuropathic facial pain condition. Assessment of treatment effectiveness is primarily clinical, given the paucity of investigational tools to assess trigeminal nerve changes. Since diffusion tensor imaging (DTI) provides information on white matter microstructure, we explored the feasibility of trigeminal nerve tractography and assessment of DTI parameters to study microstructural changes after treatment. We hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“…Our current protocol does not enable reliable follow-up DTI analyses after MVD (as it is described after radiosurgery), 14 which most likely is due to the artifacts caused by the surgical procedure itself.…”
Section: Technical Limitationsmentioning
confidence: 99%
“…Our current protocol does not enable reliable follow-up DTI analyses after MVD (as it is described after radiosurgery), 14 which most likely is due to the artifacts caused by the surgical procedure itself.…”
Section: Technical Limitationsmentioning
confidence: 99%
“…Radiosurgery has been demonstrated to induce demyelination both in experimental models [18] and in autopsy [19]. This finding has been confirmed by tractography examinations [20].…”
Section: Tnmentioning
confidence: 71%
“…, ventrointermediate nucleus (VIM), capsulotomy, trigeminal neuralgia (TN), etc.] with a high dose (maximum 80-140 Gy) or to target a large volume of tissue (i.e., 5-9 cc in epilepsy radiosurgery) with a moderate dose (17)(18)(19)(20)(21)(22)(23)(24) Gy at the marginal isodose).…”
Section: Introductionmentioning
confidence: 99%
“…Of the studies examining FA by comparing the affected and unaffected sides in patients and controls, two [6, 35] found significant decreases in FA on both sides while four of the studies [27, 32, 36, 42] found a significantly lower FA only in the affected side. Hodaie et al [38] and DeSouza et al [27] compared FA values as measured before and after surgery, with Hodaie’s study recording a significant decrease in FA after surgery and DeSouza’s study describing a significant increase in FA after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [35, 36] found significant increases in the RD when comparing patients to controls in both their affected and unaffected sides, while another two studies [27, 42] measured significance on the affected side of the patients compared to controls, and another study [41] did not find a significant difference in either category. Hodaie et al [38] and DeSouza et al [27] found significant differences in RD when comparing the affected side before and after surgery; Hodaie found a significant increase while DeSouza found a significant decrease.…”
Section: Resultsmentioning
confidence: 99%